High Life Satisfaction: Exploring the Role of Health, Social Integration and Perceived Safety among Mexican Midlife and Older Adults. Issue 5 (4th July 2019) - Camacho, David; Lee, Yookyong; Bhattacharya, Anindita; Vargas, Laura X.; Kimberly, Laura; Lukens, Ellen
ABSTRACT: We sought to investigate the relationship of high life satisfaction with important physical health, mental health, social integration and perceived safety factors among midlife and older Mexican adults. We examined 2, 200 midlife and older adults (aged 50–101 years) from the Mexican arm of the Study on global AGEing and adult health (SAGE) and used binary logistic regression models to identify key factors associated with high LSA. Our final logistic regression model revealed self-rated health, affect, interpersonal activities and perceived safety on street to be significantly associated with high life satisfaction. Results from this study add to the nascent literature on subjective well-being of midlife and older Mexicans. Although social work with older adults is not well established in Mexico, researchers and practitioners should collaborate on the development and implementation of social worker-led strategies for prevention and intervention to enhance well-being among midlife and older Mexicans.